SERUM NOx AND RBC LYSATE SOD LEVELS IN DIABETIC PATIENTS AND THEIR RELATION WITH DURATION OF DIABETES MELLITUS - P, Renuka; CR, NAVEEN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Oxidative stress is one of the major causes for complications in diabetic patients. Oxidative stress might be due to an imbalance in elimination and production of free radicals. Nitric oxide (NO) is a reactive oxygen species (RNS) and a potent vasodilator. When NO reacts with superoxide anion, it forms RNS. Superoxide dismutase (SOD) is an antioxidant enzyme which eliminates O2–. Methods: In the present study, 53 diabetic patients have been selected randomly and grouped into two groups based on the diabetic duration to evaluate the effect of duration on oxidative stress. Results: Red blood cells lysate SOD (4.745±1.047) and serum NO (52.2±25.8) are increased in diabetic patients compared with healthy controls. However, when compared between groups of different diabetic duration, SOD is decreased whereas NO is increased. Conclusion: Decrease in SOD activity might be due to the loss of its activity by glycation, whereas increase in NO might be due to the induction of endothelial NO synthase by glucose. Keywords: Diabetes mellitus, Nitric oxide, Oxidative stress, Superoxide dismutase. INTRODUCTION